Systems Biology 2019
DOI: 10.5772/intechopen.80312
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genomic Data for PCR Screening of Bet v 1 Conserved Sequence in Clinically Relevant Plant Species

Abstract: Bet v 1 is a highly immunogenic protein, which is the main cause of sensitivity to birch pollen and is described as the main birch allergen. Despite the structural similarity, Bet v 1 homologs show different properties and immunoreactivity. Here, the bioinformatic algorithms were applied for known Bet v 1 homologous nucleic acids sequences to find homology and conserved regions. Genomic sequences of PR proteins of two different fruit species, which allergens belong to PR proteins of the same type as Bet v 1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The Rub i 1 and Rub i 3 allergens in raspberry (Rubus idaeus L.) belong to the PR-10 group (17 kDa) and are homologous to the major birch pollen Bet v1 [12]. The biological function of these raspberry allergens is still unknown, and their protein sequence is highly variable within the same species [13]. A high degree of structural homology has been demonstrated between Fra a 1 (strawberry), Mal d 1 (apple) and Bet v 1 from birch [14,15] and between PR-10 proteins from different Rosaceae fruits [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Rub i 1 and Rub i 3 allergens in raspberry (Rubus idaeus L.) belong to the PR-10 group (17 kDa) and are homologous to the major birch pollen Bet v1 [12]. The biological function of these raspberry allergens is still unknown, and their protein sequence is highly variable within the same species [13]. A high degree of structural homology has been demonstrated between Fra a 1 (strawberry), Mal d 1 (apple) and Bet v 1 from birch [14,15] and between PR-10 proteins from different Rosaceae fruits [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Žiarovská and co-authors, they performed an analysis where allergen Bet v 1 homologs were identified in a range of 30 plant species. These species included Ficus carica, Carica papaya, Pyrus communis, Punica granatum, Vaccinium myrtillus, Ananas comosus, Citrus reticulata, Annona cherimola, Castanea sativa, and Citrus × limon [17]. Notably, the study also investigated Citrus sinensis, the focus of our own investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the Bet v 1 homologs is increasing, but the knowledge of the ypr10 gene and its potential applicability in different genomic techniques is still limited. However, a certain percentage of homology has been found [17].…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with defense and developmental processes and act on plasma membrane permeabilization of pathogens (Ruiz-Medrano et al 1992;Kitajima and Sato 1999;Liu et al 2010;Jesús-Pires et al 2020). Meanwhile, BET v1-like genes comprise the pathogenesisrelated protein 10 (PR10) family which is associated with plant defense functions in response to biotic and abiotic stresses and allergens (Hoffmann-Sommergruber et al 1997;Liu and Ekramoddoullah 2006;Wen et al 1997;Žiarovská and Zeleňáková 2018;Santoni et al 2019).…”
Section: Discussionmentioning
confidence: 99%